Competency-Based Assessment in Latin American Medical Education: A Scoping Review and Thematic Analysis. - Lehmann Kreisberg, Tania; Álvarez Salazar, Sophia; Silva Silva, Aylén (Spanish Journal of Medical Education, 2026)
Objective: To map the strategies, tools, and approaches used to assess competencies in medical education within undergraduate and graduate programs in Latin American countries. Introduction: Competency-based medical education is the predominant model worldwide. Its implementation in Latin America has driven significant curricular changes; however, it faces contextual challenges and a diversity of assessment approaches that require analysis. Inclusion criteria: Studies in Spanish or English (2011–2024) focusing on undergraduate or graduate medical students in Latin American countries, within the framework of competency assessment, were included. Methods: A scoping review was conducted in SciELO, Scopus, and Web of Science following the Arksey and O’Malley protocol and the PRISMA-ScR statement. The data underwent a descriptive thematic analysis. Results: Of 395 identified articles, 23 studies from eight countries were included, notably Mexico, Brazil, and Chile. The predominant method was the Objective Structured Clinical Examination (n=17), including virtual modalities. Other identified instruments were the Script Concordance Test, Objective Structured Assessment of Technical Skills, and 360° Feedback Questionnaire. The most frequently assessed domains were patient care and medical knowledge. Conclusions: Competency assessment in Latin America focuses primarily on the OSCE, a valuable tool but one that is insufficient given the current complexity of competencies. Although progress is being made toward multimodal assessment systems, further exploration of emerging methods and the validity and contextual applicability of these instruments is needed.